Effect of Nutrition Education Regarding Food Safety and Hygiene on Knowledge, Attitude and Practice (KAP) of Street Beverage Vendors of South Delhi (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
This study analyses the Knowledge, Attitude, Practice (KAP) and Observation regarding hygiene, safety and handling of food and to assess the effect of nutrition education (with developed aids) on street beverage vendors (SBV, n =100). It was a randomized controltrial in which street beverage vendors of Delhi, India was included. The SBV were divided into a control group (CG), n=50 (did not receive any nutrition education) and experimental group (EG), n=50. Nutrition education was given with the developed aids tothe EG only. After one- month of intervention KAP was assessed again for both the groups. Results revealed Knowledge score was 10.90±3.85 (poor), Attitude score was - 6.44±5.65 (poor) Practice score was 8.47± 2.58 (poor) and observation score was 16.46±4.74 (poor) of all SBV. At baseline both the groups (CG and EG) were comparable. Post nutrition education results showed an increase in the Knowledge of the EG (11.96 vs. 17.80, p=